2010
DOI: 10.3109/02699200903581042
|View full text |Cite
|
Sign up to set email alerts
|

The effect of speaking rate on velopharyngeal function in healthy speakers

Abstract: This study investigated the effect of speaking rate on aerodynamic and acoustic measures of velopharyngeal (VP) function in 27 adult speakers (14 M, 13 F). The pressure-flow method (Warren & Dubois, 1964) was used to collect aerodynamic data of /m/ and /p/ segments in the word "hamper" and the utterances "Mama made some lemon jam" (MMJ) and "Buy Bobby a puppy" (BBP). A Nasometer was used to collect nasalance scores and nasalance distance for MMJ and BBP. Measures were collected under 4 speaking rate conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 53 publications
2
26
1
Order By: Relevance
“…First, subjects were assigned to a particular dialect based upon self-report that they were native to their respective dialectical region. Although Gauster, Yunusova, and Zajac (2010) reported that aerodynamic and acoustic measures of velopharyngeal function were not affected by speaking rate variations in healthy subjects, studies by Dwyer, Robb, O'Beirne, and Gilbert (2009) and Goberman, Selby, and Gilbert (2001) have reported that measures of perceived nasality tend to decrease with increased speaking rate (and vice versa) in both hearing impaired and typical subjects, respectively. Future studies may employ the methods of Kavanagh et al (1994) in which consensus ratings on linguistically specified phonological criteria were used to confirm dialectical categorization.…”
Section: Discussionmentioning
confidence: 97%
“…First, subjects were assigned to a particular dialect based upon self-report that they were native to their respective dialectical region. Although Gauster, Yunusova, and Zajac (2010) reported that aerodynamic and acoustic measures of velopharyngeal function were not affected by speaking rate variations in healthy subjects, studies by Dwyer, Robb, O'Beirne, and Gilbert (2009) and Goberman, Selby, and Gilbert (2001) have reported that measures of perceived nasality tend to decrease with increased speaking rate (and vice versa) in both hearing impaired and typical subjects, respectively. Future studies may employ the methods of Kavanagh et al (1994) in which consensus ratings on linguistically specified phonological criteria were used to confirm dialectical categorization.…”
Section: Discussionmentioning
confidence: 97%
“…The poor responsivity of the resonatory predictor may be, in part, because the slowing of speech allowed for oropharyngeal adjustments that confounded the effect of velopharyngeal inefficacy on the measures of nasal airflow and nasalance that comprised the resonatory predictor [57]. As disease progressed, however, oropharyngeal adjustments may become unavailable so that the confounding effect was removed, resulting in rapid declines in the resonatory measures regardless of the continuous slowing of speaking rate [45]. …”
Section: Discussionmentioning
confidence: 99%
“…To obtain all other measures, the PAS was used, which collected nasal airflow by fitting a nasal mask around the participant's nose and recorded intraoral air pressure by placing a disposable pressure-sensing tube in the participant's mouth. Based on the recording, a variety of aerodynamic measures that assess velopharyngeal integrity including peak oral air pressure and peak nasal airflow during /p/ and /m/ and the lag between /m/ and /p/ in “hamper” were measured by the PAS software [45, 46]. …”
Section: Methodsmentioning
confidence: 99%
“…An average of these five productions is obtained to represent Ps during speech. f. Because Ps covaries with sound pressure level (SPL) 4,5 , the SPL is also collected for each syllable. It is used subsequently as a covariate during analyses.…”
Section: Respiratory Subsystem/ Breathing For Speechmentioning
confidence: 99%